Compound heterozygous TRPV4 mutations in two siblings with a complex phenotype including severe intellectual disability and neuropathy. Issue 11 (12th September 2017) - Thibodeau, My Linh; Peters, Colin H.; Townsend, Katelin N.; Shen, Yaoqing; Hendson, Glenda; Adam, Shelin; Selby, Kathryn; Macleod, Patrick M.; Gershome, Cynthia; Ruben, Peter; Jones, Steven J. M.; ,; et al.
Abstract : TRPV4 encodes a polymodal calcium‐permeable plasma membrane channel. Dominant pathogenic mutations in TRPV4 lead to a wide spectrum of abnormal phenotypes. This is the first report of biallelic TRPV4 mutations and we describe two compound heterozygous siblings presenting with a complex phenotype including severe neuromuscular involvement. In light of previously well described dominant inheritance for TRPV4 ‐related neuromuscular disease, our study suggests a role for compound heterozygosity and loss‐of‐function as a potential novel disease mechanism for this group of disorders. Profound intellectual disability was also noted in both affected children, suggesting that TRPV4 may be necessary for normal brain development.